1983
DOI: 10.1017/s0022112083002293
|View full text |Cite
|
Sign up to set email alerts
|

Fully developed periodic turbulent pipe flow. Part 2. The detailed structure of the flow

Abstract: The main experimental results of the study of periodic turbulent pipe flow have been described in Part 1 of this report. In this second part, these experimental data are examined in greater detail to understand the effect of imposed oscillation on the flow structure, at moderate to large oscillation frequencies. Data on phase and amplitude and energy spectrum are used to study the effect of the imposed oscillation on the turbulence structure at these interactive frequencies of oscillation. Additional experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(38 citation statements)
references
References 11 publications
3
30
2
3
Order By: Relevance
“…Both cases show that the turbulence intensity maintains the same phase lag relative to the velocity. This observation is in excellent agreement with results shown by Ramaprian and Tu, 20 but one should notice that their results concerned the centerline fluctuations only. Akhavan et al 38 report the turbulent kinetic energy integrated over the cross section, but these results are opposite to the results shown here.…”
Section: -12supporting
confidence: 92%
“…Both cases show that the turbulence intensity maintains the same phase lag relative to the velocity. This observation is in excellent agreement with results shown by Ramaprian and Tu, 20 but one should notice that their results concerned the centerline fluctuations only. Akhavan et al 38 report the turbulent kinetic energy integrated over the cross section, but these results are opposite to the results shown here.…”
Section: -12supporting
confidence: 92%
“…Ramaprian and Tu (1983) found that for sufficiently high frequencies, the time-averaged flow variables, e.g., velocity, wall shear stresses, and power loss due to friction, were affected by the imposed unsteadiness. They also concluded that, from their computations, a quasi-steady turbulence model cannot adequately describe unsteady flow conditions, at least for high frequencies.…”
Section: Introductionmentioning
confidence: 97%
“…The problems of periodic turbulent internal flow have been studied by many research workers experimentally as well as computationally (Hershey and Im 1968;Hino et al 1983;Hino et al 1976;Mizushina et al 1975;Ohmi et al 1982aOhmi et al , 1982bRamaprian and Tu 1983;Sarpkaya 1966). The periodic flow can be divided into two classes: (1) unsteady flow with nonzero mean velocity and (2) unsteady flow with zero mean velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and numerical studies of unsteady turbulent pipe (Mizushina et al, 1973;Ramaprian and Tu, 1983;Shemer et al, 1985) and channel (Tardu et al, 1994;Piomelli, 2001, 2002) flows have focused on periodic pulsating flows rather than non-periodic transient ones due to their practical applications concerned and the easy generation of the periodic flows. Mizushina et al (1973), Ramaprian and Tu (1983), Shemer et al (1985), and Tardu et al (1994) have found that, in pulsating turbulent flow experiments, the effects of the pulsation frequency and the mean flow rate were significant to the turbulence whereas that of amplitude was small.…”
Section: Introductionmentioning
confidence: 99%
“…Mizushina et al (1973), Ramaprian and Tu (1983), Shemer et al (1985), and Tardu et al (1994) have found that, in pulsating turbulent flow experiments, the effects of the pulsation frequency and the mean flow rate were significant to the turbulence whereas that of amplitude was small. Piomelli (2001, 2002) performed a large-eddy simulations (LES) of pulsating channel flow and subsequently tested the capability of Reynolds-avegared Navier-Stokes (RANS) equations simulations.…”
Section: Introductionmentioning
confidence: 99%